BENTUK, MAKNA, DAN FUNGSI KASANA KAYAU PADA MASYARAKAT DAYAK NGAJU DI KABUPATEN KATINGAN (THE FORM, MEANING, AND FUNCTION OF THE KASANA KAYAU AT DAYAK NGAJU PEOPLE IN KATINGAN REGENCY) - Lureyancee Lureyancee (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2018)
AbstractThe form, meaning, and function of the Kasana Kayau at Dayak Ngaju people in Katingan regency.The purpose of the study are (1) to describe the form of Kasana Kayau at Dayak Ngaju people inKatingan regency; (2) to describe the meaning of Kasana Kayau at Dayak Ngaju people in Katinganregency; (3) to describe the function of Kasana Kayau at Dayak Ngaju people in Katingan regency. Thequalitative method is chosen in order to describe of how the form, meaning, and function of KasanaKayau verbal tradition. This method is a method that is used to describe the fact, data, and materialobject quantitatively. The description does not refer to a specific value but it is based on such expressionof language in order to have right and systematic interpretation. Furthermore, this study is also usingspecific technic of data collection, that are (1) recording technic, both of audio and audiovisual; (2) takingnote; (3) interview; (4) library studied and documents analysis. As the result of the study, Kasana Kayauis in the form of freestyle poem which it does not refer to the rule of the old one, such as the number ofline, words, syllable, and rhyme. However, Kasana Kayau is still built in based on theme, sound, line,distich and diction. Furthermore, the result of the study which refers to the meaning of Kasana Kayau“Peteh Akan Anak SAkula”,”Mandahen Kapakat Helu”, and “Maningak Panganten”, are denotative andConnotative meaning. Then regarding to the function of Kasana Kayau “Peteh Akan Anak Sekula”, itcovers giving information, support, and spirit. Kasana Kayau “Mandehen Hapakat Helu” function is togive advice, present such moral value of live that are patience and firmness. It also provide it listenerswith advice and message.Key words: form, meaning, function, kasana kayauAbstrakBentuk, Makna, dan Fungsi Kasana Kayau pada Masyarakat Dayak Ngaju di Kabupaten Katingan.Penelitian ini bertujuan untuk (1) mendeskripsikan bentuk kasana kayau pada masyarakat Dayak Ngajudi Kabupaten Katingan; (2) mendeskripsikan makna kasana kayau pada masyarakat Dayak Ngaju diKabupaten Katingan; dan (3) mendeskripsikan fungsi kasana kayau pada masyarakat Dayak Ngaju diKabupaten Katingan. Metode penelitian ini adalah kualitatif yaitu metode yang memberikan gambarantentang fakta, data, dan objek material. Bukan berupa bentuk angka-angka tetapi ungkapan bahasaapapun bentuknya melalui interpretasi yang tepat dan sistematis. Teknik pengumpulan data dalampenelitian ini menggunakan: (1) teknik perekaman, baik audio maupun audiovisual, (2) pencatatan,58(3) wawancara yang mendalam, (4) studi kepustakaan dan analisis dokumentasi. Hasil penelitianmengenai bentuk dalam kasana kayau yang berjudul “Peteh akan Anak Sakula”, “Mandahen KapakatHelu”, dan “Maningak Panganten”, meliputi: tema, bunyi, baris, bait, dan diksi. Hasil penelitian maknayang terkandung dalam kasana kayau “Peteh akan Anak Sakula”, “Mandahen Kapakat Helu”, dan“Maningak Panganten”, adalah makna denotatif dan makna konotatif. Hasil penelitian mengenaifungsi kasana kayau “Peteh akan Anak Sakula” ini meliputi: memberi motivasi, memberi dorongan,dan memberi semangat. Fungsi kasana kayau “Mandehen Kapakat Helu” meliputi: memberi nasihat,pemersatu, dan saling menghormati. Fungsi Kasana kayau “Maningak Panganten” meliputi: memberinasihat, mengajarkan tentang hidup harus sabar dan tabah, memberi wejangan, dan memberi pesan.Kata-kata kunci: bentuk, makna, fungsi, kasana kayau